Analysis of Correlation between an Accelerometer-Based Algorithm for Detecting Parkinsonian Gait and UPDRS Subscales - Rodríguez-Molinero, Alejandro; Samà, Albert; Pérez-López, Carlos; Rodríguez-Martín, Daniel; Alcaine, Sheila; Mestre, Berta; Quispe, Paola; Giuliani, Benedetta; Vainstein, Gabriel; Browne, Patrick; Sweeney, Dean; Quinlan, Leo R.; et al. (Frontiers in Neurology, 2017)
Background Our group earlier developed a small monitoring device, which uses accelerometer measurements to accurately detect motor fluctuations in patients with Parkinson’s (On and Off state) based on an algorithm that characterizes gait through the frequency content of strides. To further validate the algorithm, we studied the correlation of its outputs with the motor section of the Unified Parkinson's Disease Rating Scale (UPDRS-III). Method Seventy-five patients suffering from Parkinson’s disease were asked to walk both in the Off and the On phase while wearing the inertial sensor on the waist. Additionally, all patients were administered the motor section of the UPDRS in both motor phases. Tests were conducted at the patient’s home. Convergence between the algorithm and the scale was evaluated by using the Spearman’s correlation coefficient. Results Correlation with the UPDRS-III was moderate (rho -0.56; p<0.001). Correlation between the algorithm outputs and the gait item in the UPDRS-III was good (rho -0.73; p<0.001). The factorial analysis of the UPDRS-III has repeatedly shown that several of its items can be clustered under the so-called Factor 1: “Axial function, balance, and gait”. The correlation between the algorithm outputs and this factor of the UPDRS-III was -0.67 (p<0.01). Conclusions The observation that the algorithm outputs are linearly correlated with the UPDRS-III scale suggests that this algorithm might be a useful tool for monitoring patients with Parkinson’s disease and motor fluctuations.